1999
DOI: 10.1046/j.1365-2265.1999.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences on quality of life in GH deficient adults and their effect on response to treatment

Abstract: Baseline QOL as assessed by self-rating questionnaires is influenced by the age of onset of the GH deficiency, adult onset patients expressing the greater distress. Improvements in QOL scores are influenced by both baseline score and to a lesser extent the age of onset of GHD, the greater improvement being observed in childhood onset patients. The degree of improvement was observed to be independent of gender, pathology and number of pituitary hormone deficits. In a cohort selected by subjectively impaired QOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 23 publications
7
63
2
1
Order By: Relevance
“…This differential responsiveness by onset type may be influenced by differences between AO and CO patients in the degree of baseline impairment in these domains. QoL improvements under GH replacement have in fact been reported to be more pronounced in patients with more severe impairment at baseline (21). In our multivariate model, although the change score for physical functioning was greater in patients with lower baseline scores, this was not the case for general health, for which baseline status did not influence changes despite considerable baseline differences between onsets.…”
Section: Discussionmentioning
confidence: 46%
“…This differential responsiveness by onset type may be influenced by differences between AO and CO patients in the degree of baseline impairment in these domains. QoL improvements under GH replacement have in fact been reported to be more pronounced in patients with more severe impairment at baseline (21). In our multivariate model, although the change score for physical functioning was greater in patients with lower baseline scores, this was not the case for general health, for which baseline status did not influence changes despite considerable baseline differences between onsets.…”
Section: Discussionmentioning
confidence: 46%
“…However, several studies have examined correlations between baseline variables (i.e., before the start of GH replacement therapy) and later improvement in QOL [26] or baseline predictors of later improvement in QOL [27]. In a KIMS database study, Svensson et al [26] found that baseline QOL (assessed using the QOL-Assessment of GHD in Adults instrument [QOL-AGHDA]), serum HDL-C concentrations, and the duration of hypopituitarism were negatively correlated with QOL at 12 months.…”
Section: Funding Supportmentioning
confidence: 99%
“…In a KIMS database study, Svensson et al [26] found that baseline QOL (assessed using the QOL-Assessment of GHD in Adults instrument [QOL-AGHDA]), serum HDL-C concentrations, and the duration of hypopituitarism were negatively correlated with QOL at 12 months. In a small-scale (N = 65), open-label study, Murray et al [27] found that baseline QOL (QOL-AGHDA/Psychological General Wellbeing Schedule) and the age of onset of GHD were the most important predictors of improvement in QOL after up to 24 months of GH replacement therapy as determined by multiple linear regression analysis. The findings from these studies suggest that some baseline variables may be associated with long-term changes in QOL after the start of GH replacement therapy, but are clearly not directly comparable with the findings of our study given the different timing of assessments.…”
Section: Funding Supportmentioning
confidence: 99%
“…Curiously and unexplained, severe impairment of QoL is more frequently seen in adult patients with adult onset (AO) GHD compared with patients with childhood onset (CO) GHD (23).…”
Section: Quality Of Lifementioning
confidence: 99%